Seismic Analysis Of G+20 Irregular Building With Top 5 Floor Swimming Pool - Mariya Tahreem M. H., A.; U. S., Ansari; . Faizan Ahmed, A (Journal of Neonatal Surgery, 2025)
This study focuses on the seismic analysis of a G+20 irregular building with a top 5- floor swimming pool, utilizing the Response Spectrum Method in ETABS software for seismic evaluation in Seismic Zone V. The building’s irregularities, especially due to the presence of a swimming pool at the upper floors, were carefully modeled to simulate their effect on the building’s seismic response. The analysis aimed to evaluate the displacement, overturning moments, base shear, and storey drift under seismic loading conditions, considering the dynamic interaction between the swimming pool and the building structure. The study shows that the irregular geometries, particularly in the Squared-shaped, C-shaped, I-shaped and L-shaped configurations, lead to higher displacement and torsional effects when subjected to seismic forces, while the square- shaped building exhibited the best performance in minimizing these effects. The findings from the seismic analysis demonstrate that although the addition of a swimming pool increases the seismic response, all structural configurations remain within the permissible limits prescribed by IS 875 and IS 1893-2016. The response spectrum method in ETABS provided a comprehensive understanding of the building's behavior under seismic loading, including the influence of irregularity and additional loads from the swimming pool. The results highlight the importance of incorporating dynamic effects such as base shear, overturning moment, and storey drift when designing tall buildings with additional loads like swimming pools, ensuring structural integrity and stability in high seismic zones like Zone V.